MODIFIKASI NUTRISI PADA MEDIA HIDROPONIK UNTUK BUDIDAYA TANAMAN SAWI - Mohamad Ihsan Tri Rahayu (Universitas Islam Batik Surakarta, 2014)
The research objective was to know the effect concentration of foliar fertilizer toward growth and yield of mustard plant (Brassica juncea) which growth in media with several kind of organic liquid fertilizer on hidroponic methode. The experiment was conducted in glass house which arrange as factorial Completely Randomized Design with two factors as treatment that were: concentration of liquid nutritionon media which have four levels: 1,5 cc lt-1water, 2,5 cc lt-1water, 3,5 cc lt-1water, and 4,5 cc lt-1water. The second factor was application kind of foliar liquid organic fertilizer there were three kinds: organic fertilizer of 2N, organic fertilizer of NASA, and organic fertilizer of Solusi. The mustard planted in hidroponic system and several parameters of plant growth and yield were observed. Result of the research showed that the concentration of nutrition treatment and also kind of liquid organic source gave significant influence on growth and yield of mustard, but no interaction between the treatment. The best concentration for mustard was reached on 3,5 cc lt-1 water of liquid nutrition and 2N organic fertilizer was the best kind of foliar liquid organic for that hidroponic system.